Prevalence and Risk Factors of Musculoskeletal Disorders Among Intensive Care Unit Nurses: A Case Study in a Hospital, Bangkok - Pojjariyaporn, Jirameth; Sithisarankul, Pornchai; Rattananupong, Thanapoom (Journal of The Royal Thai Army Nurses, 2024)
The purpose of this research is to reveal prevalence and risk factors of musculoskeletal disorders. The researcher distribute questionnaires and assess ergonomic risk factors for each type of work. The information obtained will be used to analyze relationships. The prevalence of musculoskeletal disorders in the past 12 months was 79.2% and 72.3% in the past 7 days, respectively. The highest affected region was lower back. Risk factors of musculoskeletal disorders include age, exercise habits, working hours and ergonomic risks. For each type of work, ergonomic risks in neck and back region were found to be associated with musculoskeletal disorder. Therefore, there must be improvement each type of working condition to reduce the level of ergonomic risk, especially the neck and back regions, Including workload and working hours to suit each individual. Training on proper working postures and exercise to prevent and reduce musculoskeletal disorders.